2013
DOI: 10.4236/jct.2013.42a049
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategy for Recurrent Multiple Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) has some unique characteristics in the digestive organ cancer. Therefore it is very important to select an appropriate treatment for recurrent HCC according to several situations such as the type of recurrence, previous treatments and conditions of patient. This article is a review of the concept of recurrent multiple HCC and its therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Different from other cancers, multifocal tumors are very common in PLC [ 2 , 3 ]. A recent national survey in Japan showed that half of the PLCs, especially HCC, were multiple lesions [ 4 ]. Chronic liver damage, such as that caused by chronic hepatitis and liver cirrhosis, is closely associated with the occurrence of both HCC and ICC [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different from other cancers, multifocal tumors are very common in PLC [ 2 , 3 ]. A recent national survey in Japan showed that half of the PLCs, especially HCC, were multiple lesions [ 4 ]. Chronic liver damage, such as that caused by chronic hepatitis and liver cirrhosis, is closely associated with the occurrence of both HCC and ICC [ 5 ].…”
Section: Introductionmentioning
confidence: 99%